An Analysis of Islamic Education Teachers’ Readiness in Using Educational Technology at the Madrasah Ibtidaiyah (Islamic Elementary School) Level - Nova Andriyani; Mokhamad Choirul Hudha (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: An Analysis of Islamic Education Teachers’ Readiness in Using Educational Technology at the Madrasah Ibtidaiyah (Islamic Elementary School) LevelObjective: This study analyzes teachers' readiness to use learning technology in religious clumps at MI Muhammadiyah Ketepung. Methods: This study used a qualitative method with an analytic descriptive approach. Data were collected through observation, interviews, and documentation. Data analysis through four stages: data collection, data reduction, data presentation, and conclusion drawing. Results: Teacher readiness is still limited due to a lack of understanding of technology, access, facilities, and infrastructure. It is recommended that educational institutions provide intensive training and mentoring, improve access to technology, and develop policies that support the use of technology. Conclusion: Although Islamic education teachers in Madrasah Ibtidaiyah are willing to use learning technology, they face various obstacles in its implementation. Contribution: This research provides practical input for Islamic education teachers in Madrasah Ibtidaiyah to improve the quality of their teaching by utilizing learning technology on the characteristics of religious subjects.INDONESIAN: Analisis Kesiapan Guru Pendidikan Agama Islam dalam Penggunaan Teknologi Pembelajaran tingkat Madrasah IbtidaiyahTujuan: Penelitian ini bertujuan untuk menganalisis kesiapan guru dalam penggunaan teknologi pembelajaran pada rumpun keagamaan di MI Muhammadiyah Ketepung. Metode: Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif analitik. Data dikumpulkan melalui observasi, wawancara, serta dokumentasi. Analsisi data melalui empat tahapan yaitu pengumpulan data, reduksi data, penyajian data, serta penarikan kesimpulan. Hasil: Kesiapan guru masih terbatas karena kurangnya pemahaman teknologi, akses, serta sarana dan prasarana. Disarankan agar lembaga pendidikan memberikan pelatihan dan pendampingan intensif, meningkatkan akses teknologi, dan mengembangkan kebijakan yang mendukung penggunaan teknologi. Kesimpulan: Meskipun guru pendidikan agama Islam di Madrasah Ibtidaiyah berkeinginan untuk menggunakan teknologi pembelajaran, namun mereka masih menghadapi berbagai kendala dalam implementasinya. Kontribusi: Penelitian ini memberikan masukan praktis bagi guru Pendidikan Agama Islam di Madrasah Ibtidaiyah untuk meningkatkan kualitas pengajaran mereka dengan memanfaatkan teknologi pembelajaran yang sesuai dengan karakteristik mata pelajaran agama.